Rounding [videorecording (Blu-Ray)] - Thompson, Alex (Film director); Thompson, Christopher; Smallwood, Namir; Potts, Michael (Performer); Flanigan, Sidney (Music Box Selects, 2025)
After a traumatic incident, a driven young medical resident transfers to a rural hospital for a fresh start, but the demons of his past start to catch up to him when he becomes consumed by the case of a patient with mysterious symptoms.